Analisis Transaksi Menggunakan Go-Pay Pada Kedai Bakso Di Kota Malang - Arifin, Zainul (Arthavidya Jurnal Ilmiah Ekonomi, 2020)
Abstract: Go-Pay is a form of Fintech, which is currently a trend both in terms of equipment and business. Its practical, safe and easy use encourages people to use this service. Go-Pay is currently aspired to be a one-stop service application where users can order various types of services from just one application.The purpose of this study was to determine how the pattern of use of Go-Pay by Kedai Bakso and the factors that support and inhibit its use. To get these results, Adaptive Structuration Theory (AST) is used because the structure contained in this model can be modified according to the needs of the object under study In implementing fintech, there were needs that had arisen before the store manager finally decided to implement fintech. The decision was supported by offers from service providers, as well as information from fellow business actors. After implementing fintech, costs arise as a result of implementing services. So businesses need to make price adjustments to their products. In the end, businesses maintain services that benefit their business. Keyword: fintech, payment, transaction, umkm